Knowledge, attitudes and prevention practices regarding HIV/AIDS among barbers in Ho municipality, Ghana - Mercy Demaris Quarm; Jacqueline Mthembu; Khangelani Zuma; Elvis Enowbeyang Tarkang (Taylor & Francis Group, 2021)
The barbing industry poses particular public health risks if it is not conducted in a safe and hygienic manner. These risks can lead to the transmission of infectious diseases like the Human Immunodeficiency Virus (HIV) to the barbers or their clients. This study investigated the knowledge, attitudes and prevention practices regarding HIV transmission among barbers in the Ho Municipality. A descriptive cross-sectional design was employed. A pretested structured questionnaire was administered to a consented sample of barbers sampled using a multistage random sample design. Descriptive and inferential statistics were performed using Stata version 14.0 software programme where 0.05 level was used as a measure of significance. The knowledge level of the barbers regarding HIV/AIDS was inadequate (63.6%). Knowledge was significantly associated with work experience [AOR = 13.56 (95% CI: 2.73-67.25); p = 0.001], with attitude [AOR = 4.07 (95% CI: 1.27-13.08); p = 0.018], with level of education [AOR = 10.22 (95% CI: 2.24-46.64); p = 0.003], with marital status [AOR = 0.07 (95% CI: 0.01-0.50); p = 0.008] and with number of clients per day [AOR = 0.13 (95% CI: 0.03-0.52); p = 0.004]. The attitude of barbers was also inadequate (58.7%). Attitude was significantly associated with the mode of learning the barbing profession [AOR = 0.32 (95% CI: 0.11-0.89); p = 0.029], and with level of knowledge [AOR = 5.48 (95% CI: 2.01-14.93); p = 0.001]. Majority of the participants exhibited poor prevention practices regarding HIV/AIDS (87.6%). Prevention practice was significantly associated with work experience [AOR = 24.92 (95% CI: 2.08-297.86); p = 0.011] and with level of knowledge [AOR = 12.57 (95% CI: 1.35-116.86); p = 0.026]. The barbers in Ho exhibited inadequate knowledge and attitude regarding HIV/AIDS, and also manifested poor prevention practices regarding HIV/AIDS. Programmes aimed at improving the knowledge, attitudes and prevention practices should be implemented among barbers, with focus on those without any formal education, those with less than five years work experience and those with more than ten clients a day.